Corporate Entrepreneurship as Renewal Strategy After COVID-19: The Case of Serbia - Kontic, Ljiljana; Todosijevic, Milos; Kontic, Jovan (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The main aim of the paper is to emphasis the role of corporate entrepreneurship in the strategic choice after Covid - 19 pandemic. Main proposition was that innovation and corporate entrepreneurship would be created a renewal and new growth. The study has been conducted on 287 managers and employees from various companies in Serbia. The Corporate Entrepreneurship Assessment Instrument (CEAI) has been used by written permission given by authors (Kuratko et al., 2014). The relevant statistical methods have been used for data analysis by SPSS 24.0 software. The results of factor analysis showed the key factors from CEAI questionnaire that must be included into renewal strategy in Serbian companies. The limitation and future research agenda would be presented, too.